The complex behavior of El Niño winter 2015–2016. Issue 6 (25th March 2017) - Palmeiro, F. M.; Iza, M.; Barriopedro, D.; Calvo, N.; García‐Herrera, R.
Abstract: This paper examines the outstanding characteristics of the strong 2015–2016 El Niño (EN) winter and its impact over the European region through the stratosphere. Despite being classified as a strong eastern Pacific (EP) EN event, our analysis reveals an anomalous behavior, with some signatures that are more typical of central Pacific (CP) EN events instead. They include (i) a record‐breaking value of the CP index, (ii) a stronger polar vortex in early and midwinter, due to reduced upward wave activity and a weakened Aleutian low, and (iii) the occurrence of one of the earliest stratospheric final warmings (SFWs) on record, which are more prone to occur during CP‐EN. Following the SFW, a stratospheric influence on the Euro‐Atlantic sector is reported in spring, with persistent Greenland blocking resulting in extreme precipitation over some southern European regions. Results highlight the importance of considering early SFWs as mediators of El Niño teleconnections. Key Points: The 2015‐2016 Eastern Pacific El Niño reached a record‐breaking sea surface temperature anomalies in the Central Pacific region An extremely early stratospheric final warming occurred in early March 2016, with impacts over the North Atlantic and Europe When accompanied by early stratospheric final warmings, central Pacific El Niño events have tropospheric effects in late winter and spring